Novel Mutations Associated with N-Gene Target Failure in SARS-COV-2 Genome in Iran, Case Series - Ali Maleki1, 2; Zahra Fereydouni1; Mahsa Tavakoli1; Akram Ezani3; Mirshamsedin Hosseini3; Amir Hesam Nemati1; Parastoo Yektay Sanati1; Tahmineh Jalali1, 4, 5; Mohammad Hassan Pouriayevali1, 4, 5; Mostafa Salehi-Vaziri1, 4, 5 (Journal of Medical Microbiology and Infectious Diseases)
Precision tracking and monitoring viral genome mutations are critical during a viral pandemic such as COVID-19. As molecular assays for diagnosing numerous infectious agents are being developed, RT-PCR is still deployed as the gold standard for detecting SARS-CoV-2. Despite its proofreading capability, SARS-CoV-2, like other RNA viruses, adopts several changes in its genome. If these mutations, especially deletions, occur in the target areas of primers and probes, they will hinder molecular detection methods from identifying the given gene. The authors describe the cases in which, despite the lack of the N gene detection, the ORF1ab gene was discovered with a relatively low cycle of threshold (Ct). Following sequencing, changes were discovered in the annealing region of the forward and reverse primers and probes used in the SARS-CoV-2 detection kit. Among the most significant mutations is a large deletion of 15 nucleotides in the N gene, which has never been seen in prior variants. This highlights the importance of persistent monitoring of hypervariable regions in the SARS-CoV-2 genome through sequencing and updating the molecular detection kits during the COVID-19 pandemic.